Workshop Pengenalan Quillbot Sebagai Alat Bantu Menulis - Sibghatullah Mujadidi; Siti Suharsih; Salma Syadilla; Rifa Reviana Aprillia; Elda Nabila; Ratna Suci Cahyaningrom (Jurnal Kabar Masyarakat, 2023)
Writing is an activity carried out by someone to create a written work. Writing is one of the skills that students must have. In this modern era, the use of sophisticated technology can help writing activities to create even better written works. This workshop aims to socialize Quillbot as a writing tool that can be used by students to create written works. This workshop presented two speakers. The first resource person was a teacher at SMA Negeri 6 Serang City who explained material related to scientific writing. Meanwhile, the second resource person was an UNTIRTA student who explained the material and demonstrated the use of Quillbot. Based on the results and discussions, this workshop activity really helped students to practice their writing skills.